Ionospheric Response to the 24–27 February 2023 Solar Flare and Geomagnetic Storms Over the European Region Using a Machine Learning–Based Tomographic Technique - Ting Li; Dunyong Zheng; Changyong He; Fei Ye; Pengfei Yuan; Yibin Yao; Mengguang Liao; Jian Xie (Space Weather)
Abstract Two solar flares accompanied by coronal mass ejections (CMEs) occurred on 24–25 February (DOY 055–056), 2023, resulting in a large magnetic storm on DOY 058. We reconstructed the ionospheric electron density (IED) in Europe to analyze the spatial distribution of ionosphere and its temporal evolution during this period. Computerized ionospheric tomography based on machine learning (CIT‐ML) was used to predict the IEDs of unobserved voxels. The IEDs were examined using observation data from the Swarm satellite. The CIT‐ML accuracy was 28.3% higher than the improved algebraic reconstruction technique with relaxation factor automatic search technology (IART‐AS), which effectively improved the typical ill‐posed problem of CIT. The first flare generated the Bz component of the interplanetary magnetic field (IMF), which continued southward for 13 hr, causing a small magnetic storm before the second flare occurred, resulting in an increased nighttime IED and nighttime medium‐scale traveling ionospheric disturbance (MSTID). The vertical total electron content (VTEC) and IED declined in the early stages of the main phase of the large magnetic storm, but later increased, indicating that negative‐positive biphasic storms were occurring in the ionosphere that altered the ionospheric daily cycle, resulting in the peak of the ionosphere being advanced by approximately 1.5 hr. The storms also caused nighttime MSTIDs during the main phase (DOY 057 at night) and the recovery phase (DOY 058 at night). To investigate the mechanisms of these results, we conducted a term analysis of the ion continuity equation using the Thermosphere Ionosphere Electrodynamics General Circulation Model (TIEGCM). The analysis showed that ambipolar diffusion driver nighttime MSTIDs during flares, while increased geomagnetic disturbances amplify the effects of neutral wind transport, E × B drift and chemical reactions during magnetic storms. These combined effects offset the alternating positive and negative structures induced by ambipolar diffusion, becoming the main cause of electron density variations during ionospheric storms.